2009
DOI: 10.4049/jimmunol.0802181
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus Glycopeptidolipids Mask Underlying Cell Wall Phosphatidyl-myo-Inositol Mannosides Blocking Induction of Human Macrophage TNF-α by Preventing Interaction with TLR2

Abstract: Mycobacterium abscessus causes disease in patients with structural abnormalities of the lung, and it is an emerging pathogen in patients with cystic fibrosis. Colonization of the airways by nontuberculous mycobacteria is a harbinger of invasive lung disease. Colonization is facilitated by biofilm formation, with M. abscessus glycopeptidolipids playing an important role. M. abscessus can transition between a noninvasive, biofilm-forming, smooth colony phenotype that expresses glycopeptidolipid, and an invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 36 publications
10
137
0
Order By: Relevance
“…We have postulated that this is due to GPL expression by 390S, which is supported by genetic studies demonstrating that GPL is necessary for both biofilm formation and sliding motility in Mycobacterium smegmatis, a non-pathogenic NTM (Recht et al, 2000). We have provided evidence that expression of GPL facilitates the M. abscessus colonization phenotype, but 'masks' underlying bioactive cell-wall lipids involved in virulence (Rhoades et al, 2009). In this study we have used genetic recombineering to delete the M. abscessus 390S mmpL4b gene, a gene coding for a membrane protein which has been found to play an essential role in GPL expression by NTM (Recht et al, 2000;Ripoll et al, 2007;Medjahed & Reyrat, 2009).…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…We have postulated that this is due to GPL expression by 390S, which is supported by genetic studies demonstrating that GPL is necessary for both biofilm formation and sliding motility in Mycobacterium smegmatis, a non-pathogenic NTM (Recht et al, 2000). We have provided evidence that expression of GPL facilitates the M. abscessus colonization phenotype, but 'masks' underlying bioactive cell-wall lipids involved in virulence (Rhoades et al, 2009). In this study we have used genetic recombineering to delete the M. abscessus 390S mmpL4b gene, a gene coding for a membrane protein which has been found to play an essential role in GPL expression by NTM (Recht et al, 2000;Ripoll et al, 2007;Medjahed & Reyrat, 2009).…”
Section: Introductionmentioning
confidence: 48%
“…We have demonstrated that the smooth colony phenotype of M. abscessus is due to expression of glycopeptidolipid (GPL) in the bacterial cell wall; GPL is minimally expressed by rough variants (Howard et al, 2006). We have also demonstrated that the rough variants 390R and 390V are able to grow in human macrophages and stimulate macrophage Toll-like receptor 2 (TLR2), while the 390S variant lacks these capabilities (Byrd & Lyons, 1999;Howard et al, 2006;Rhoades et al, 2009). Unlike the rough variants, the 390S variant is able to form biofilms and exhibits sliding motility.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…1,31,32 Previous studies have shown that mannose-containing glycolipids induce IL-12 production in a manner different from classical TLR ligands, 33 whereas ManLAM was shown to inhibit the production of IL-12 in human dendritic cells via an MR-dependent mechanism that interfered with TLR-based responses. 23 We examined IL12p40 production after the addition of TLR2 and MR blocking antibodies.…”
Section: Cap Sugars Derived From Manlam Are Required Tlr2 To Elicit Imentioning
confidence: 99%
“…Intracellular pathogens mediate their interactions through specific host cell receptors to facilitate host cell adherence and entry. [31][32][33] Use of particular host-cell receptors and mode of entry are determinative in specifying the subsequent intracellular fate of the organism and in directing the innate immune response. 31,36 The present novel pathogen-derived CSCBs 19 allowed investigation of how sugars themselves alter in vitro and in vivo innate immune responses.…”
Section: Immunomodulation By Pathogen Oligosaccharidesmentioning
confidence: 99%